Fabrication of TiO 2 with mesoporous structures through ultrasonic irradiation at room temperature and their photocatalytic performances - Yu, C.; Zhou, W.; Cao, F.; Li, Xin Yong; Yu, J. (2012)
A series of TiO 2 photocatalyst with well mesoporous structures and high crystallinities were rapidly fabricated by ultrasonic irradiation at room temperature. The prepared samples were characterized by physical adsorption of N 2, X-ray di_raction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The effects of the power and time of the ultrasonic irradiation on the crystallinity, surface area, pore volume and pore size of the TiO 2 were investigated. The formation mechanism for the mesoporous TiO 2 photocatalyst under ultrasonic irradiation was proposed. The photocatalytic activity of the samples was evaluated by photocatalytic degradation of methylic orange under UV light (?=365 nm) irradiation. The results showed that the increase of ultrasonic irradiation power will increase the crystallinity, pore size and dispersion of TiO 2 and decrease the size of the grain. A high photocatalytic activity was obtained in the ultrasonic fabricated samples, which could be attributed to the high crystallinity and high surface area and pore volume of the photocatalysts.